The German work : 1925 - 1938 - Hoppé, Emil O. 1878-1972 (Steidl, 2015)
Between 1925 and 1938, photographer E O Hoppe traveled the length and breadth of Germany, recording people and places at one of the most tumultuous times in the countrys history. He photographed movie stars and captains of industry, workers and peasants, and captured the birth of the Autobahn and UFA film studios in its heyday. He saw the rise of fascism, the creation of vast new suburbs, and the displacement of people from their traditional ways of life. With unprecedented access to the countrys world-famous factories and industrial installations, he witnessed Germany as few others could barreling headlong into the unknown. Moving, insightful, and deeply revealing, the full significance of Hoppes German work has been unknown until now. This volume combines photographs published in Hoppes legendary book of 1930, Deutsche Arbeit, with many new pictures never previously seen